High Malaria Prevalence among Schoolchildren on Kome Island, Tanzania - Kim, Min-Jae (Korean J Parasitol, 2015)
In order to determine the status of malaria among schoolchildren on Kome Island (Lake Victoria), near Mwanza, Tanzania, a total of 244 schoolchildren in 10 primary schools were subjected to a blood survey using the fingerprick method. The subjected schoolchildren were 123 boys and 121 girls who were 6-8 years of age. Only 1 blood smear was prepared for each child. The overall prevalence of malaria was 38.1% (93 positives), and sex difference was not remarkable. However, the positive rate was the highest in Izindabo Primary School (51.4%) followed by Isenyi Primary School (48.3%) and Bugoro Primary School (46.7%). The lowest prevalence was found in Muungano Primary School (16.7%) and Nyamiswi Primary School (16.7%). These differences were highly correlated with the location of the school on the Island; those located in the peripheral area revealed higher prevalences while those located in the central area showed lower prevalences. Plasmodium falciparum was the predominant species (38.1%; 93/244), with a small proportion of them mixed-infected with Plasmodium vivax (1.6%; 4/244). The results revealed that malaria is highly prevalent among primary schoolchildren on Kome Island, Tanzania, and there is an urgent need to control malaria in this area.